2019
DOI: 10.1007/s10766-019-00646-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Scalability of Sparse Matrix–Vector Multiplications on Phytium FT-2000+

Abstract: Understanding the scalability of parallel programs is crucial for software optimization and hardware architecture design. As HPC hardware is moving towards many-core design, it becomes increasingly difficult for a parallel program to make effective use of all available processor cores. This makes scalability analysis increasingly important. This paper presents a quantitative study for characterizing the scalability of sparse matrix-vector multiplications (SpMV) on Phytium FT-2000+, an ARM-based HPC many-core a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…To better explore the accuracy of estimation result, the coefficient of determination 2 and RMSE(root mean square deviation) are calculated, as shown in Table 1. It can be concluded that the model is less effective in predicting an instantaneous power spike.…”
Section: Overall Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To better explore the accuracy of estimation result, the coefficient of determination 2 and RMSE(root mean square deviation) are calculated, as shown in Table 1. It can be concluded that the model is less effective in predicting an instantaneous power spike.…”
Section: Overall Resultsmentioning
confidence: 99%
“…Prior work in the area of machine-learning-based systems optimisation provides evidence showing that this could be a viable means to overcome the limits in the hardware implementation [6,7,19,20,27,29,30]. Effort in this direction includes performance modeling for the FT-2000+/64 architecture [2]. We leave this as our future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the Phytium 2000+ platform, SELL is the optimal format for around 50% of the sparse matrices and ELL gives the worst performance on most of the cases. Therefore we need an adaptive scheme to help developers to choose the optimal sparse matrix format [20][21][22] .…”
Section: Overall Spmv Performancementioning
confidence: 99%
“…There are many studies showing it outperforms human-based approaches. Recent work shows that it is effective in performing parallel code optimization (Chen et al 2020;Cummins et al 2017a, b;Grewe et al 2013b;Ogilvie et al 2014;Wang et al 2014aWang et al , 2015, performance predicting (Wang and O'Boyle 2013;Zhao et al 2016), parallelism mapping (Grewe et al 2013a;Taylor et al 2017;Tournavitis et al 2009;Wang and O'Boyle 2010;Wang et al 2014bWang et al , 2015Wen et al 2014;Zhang et al 2020), and task scheduling (Emani et al 2013;Marco et al 2017;Ren et al 2017Ren et al , 2018Ren et al , 2020Sanz Marco et al 2019;Yuan et al 2019). As the many-core design becomes increasingly diverse, we believe that the machinelearning techniques provide a rigorous, automatic way for constructing optimization heuristics, which is more scalable and sustainable, compared to manually-crafted solutions.…”
Section: A Vision For the Next Decadementioning
confidence: 99%